Correlation between serum ferritin levels and attention-deficit/hyperactivity disorder symptom scores in children based on the Abbreviated Conners Teachers Rating Scale - Intan Alita Putri Tumbelaka; Hardiono Pusponegoro; Rinawati Rohsiswatmo (Indonesian Pediatric Society, 2012)
factors causing attentionô€šdefidt /hyperactivity disorder (ADHD)in children. Iron contributes to the regulation of dopamineneurotransmitter activity, thus, iron deficiency has been associatedwith ADHD. Several studies have been conducted in othercountries to assess for a correlation between serum ferritin levelsand ADHD symptom scores, but 'With varied results.Objective To examine the relationship between iron deficiency andADHD symptoms, in particular the correlation between serumferritin levels and Abbreviated Conners Teachers Rating Scale(ACTRS) scores in children v.ith ADHD.Methods T his crossô€šsectional study was performed in childrenaged 5ô€š 12 years who were newly diagnosed lith ADHD. Subjectswere recruited from the Klinik Anakku Kelapa Gading, theNeurology Outpatient Clinic, the Growth and Developmentô€šSocial Pediatrics Outpatient Clinic, and the Integrated ChildClinic of Cipto Mangunkusumo Hospital. ADHD diagnoses wereestablished using Diagnostic and Statistical Manual of MentalDisorders, 4th edition (DSMô€šIV). Subjects' parents and teacherswere asked to complete the ACTRS instrument sheet. Venousblood specimens were obtained for peripheral blood and serumferritin level tests.Results Of the 33 subjects recruited, 23 were male. Subjects' agesranged from 5ô€š 12 years, lith a median age of onset of 4 (range2ô€š 10) years. The combined type of ADHD (with inattention andhyperactivityô€šimpulsivity) was more commonly found (20/33)in our subjects. T he mean serum ferritin was 51.31 (SD 27.7)ng/mL. Using 20 ng/mL as the serum ferritin cutoff value, 5/33subjects were considered to be iron deficient. Median ACTRSscore by parents and teachers were 15 and 15, respectively. Higherscores were found in the combined type subject group than in theinattention type subject group. Median serum ferritin levels ofthe two ADHD type groups were similar. Median ACTRS scoresof parents and teachers tended to be higher in the ironô€šdeficientgroup (16 and 16, respectively) than in the normal serum irongroup (14.5 and 12.5, respectively). Serum ferritin level showedno correlation (r=ô€š0.243; P=0.086) to the parents' ACTRSscore, and no correlation (r=ô€š.057; P=0.377) to the teachers'ACTRS score.Conclusion Serum ferritin level showed no correlation to ACTRSscores of parents and teachers, respectively. However, the medianACTRS score was higher in the ironô€šdeficiency group than in thenormal iron status group, suggesting that there may be a qualitativerelationship between iron deficiency and ADHD symptoms.[Paediatr lndanes. 2012;52:329-35].